Mission moves Cultivating communities of the Gospel - Nel, Malan (HTS Religion & Society Series, 2021)
This scholarly book is the final result of a team-research project, done by ten Practical Theologians from three denominations in the Reformed tradition in South Africa. The authors posed the following research problem and-question: What would be the relationship (if any) between preaching (and the liturgy of which it is a part) and the development of missional congregations? And secondly, what kind of preaching and preacher would best serve (even facilitate) such a process of missional congregational development in preaching and worship?